Paracrine effects of oocyte secreted factors and stem cell factor on porcine granulosa and theca cells in vitro - Brankin, V.; Mitchell, M.R.; Webb, B.; Hunter, M.G. (2003)
Oocyte control of granulosa and theca cell function may be mediated by several growth factors via a local feedback loop(s) between these cell types. This study examined both the role of oocyte-secreted factors on granulosa and thecal cells, cultured independently and in co-culture, and the effect of stem cell factor (SCF); a granulosa cell derived peptide that appears to have multiple roles in follicle development. Granulosa and theca cells were isolated from 2-6 mm healthy follicles of mature porcine ovaries and cultured under serum-free conditions, supplemented with: 100 ng/ml LR3 IGF-1, 10 ng/ml insulin, 100 ng/ml testosterone, 0-10 ng/ml SCF, 1 ng/ml FSH (granulosa), 0.01 ng/ml LH (theca) or 1 ng/ml FSH and 0.01 ng/ml LH (co-culture) and with/without oocyte conditioned medium (OCM) or 5 oocytes. Cells were cultured in 96 well plates for 144 h, after which viable cell numbers were determined. Medium was replaced every 48 h and spent medium analysed for steroids.Oocyte secreted factors were shown to stimulate both granulosa cell proliferation (P < 0.001) and oestradiol production (P < 0.001) by granulosa cells throughout culture. In contrast, oocyte secreted factors suppressed granulosa cell progesterone production after both 48 and 144 hours (P < 0.001). Thecal cell numbers were increased by oocyte secreted factors (P = 0.02), together with a suppression in progesterone and androstenedione synthesis after 48 hours (P < 0.001) and after 144 hours (P = 0.02), respectively. Oocyte secreted factors also increased viable cell numbers (P < 0.001) in co-cultures together with suppression of progesterone (P < 0.001) and oestradiol (P < 0.001). In granulosa cell only cultures, SCF increased progesterone production in a dose dependent manner (P < 0.001), whereas progesterone synthesis by theca cells was reduced in a dose dependent manner (P = 0.002). Co-cultured cells demonstrated an increase in progesterone production with increasing SCF dose (P < 0.001) and an increase in oestradiol synthesis at the highest dose of SCF (100 ng/ml). In summary, these findings demonstrate the presence of a co-ordinated paracrine interaction between somatic cells and germ cells, whereby oocyte derived signals interact locally to mediate granulosa and theca cell function. SCF has a role in modulating this local interaction. In conclusion, the oocyte is an effective modulator of granulosa-theca interactions, one role being the inhibition of luteinization